Electric arc furnace design and construction for metallurgical and semiconductor research. Issue 5 (February 2016) - Barbouche, M.; Hajji, M.; Ezzaouia, H.
Abstract In this work, a small electric arc furnace (EAF) was designed and constructed for the growth of silicon carbide (SiC) and metallurgical-grade silicon (MG-Si) widely used in photovoltaic and electronic applications. A new design of DC electric arc furnace was developed in order to work with powder raw materials and to optimize the temperature's homogeneity. The optimization of some parameters, such as the minimization of heat's losses, and control of furnace temperature, is a necessary step for an objective and trustworthy data acquisition which lead to produce good-quality materials. This work consists of two major parts, sizing and design part in one hand and construction and optimization part in the other hand. The sizing and design part includes not only the mechanical design of different furnace's components but also the thermal protection and the dimensioning of the reactor. It includes also the electrical design and the development of an interface in LABVIEW environment to enable mass flow controller and the solenoid valves control. It also allows the PC-based data acquisition (temperature, flow, etc.). Congestion, security, accessibility, and mobility are considered during this part. The construction and optimization part includes mechanical manufacture using locally available equipments and the assembly of the different pieces. It includes also the preliminary measurements and tests made with our furnace. The analyses by Raman spectroscopy confirm the production of silicon carbide and metallurgical silicon using this EAF.